Manajemen Pelaksanaan Kegiatan Lailatul Qadar Dalam Merekatkan Ukhuwah Islamiyah Di Masjid Taqwa Kota Parepare - Evi Saputri; Muhammad Haramain; Nurhikmah Nurhikmah (Jurnal Kajian Manajemen Dakwah, 2021)
This study focuses on the implementation of lailatul qadar activities at the Taqwa Mosque in Parepare City, the purpose of this research is to find out how the management of lailatul qadar activities in gluing ukhuwah Islamiyah congregations, and to find out things related to the sunnah prayer activities carried out on the night of lailatul qadar at the Taqwa Mosque in Parepare City. The research used is descriptive qualitative method. The approach used is a qualitative approach with qualitative data types and primary and secondary data sources. The data collection technique used in this research is the technique of observation, interviews and documentation. While the data analysis techniques used are data reduction, data presentation and drawing conclusions. The results showed that the condition of the ukhuwah Islamiyah congregation of the Taqwa Mosque in Parepare City was quite good, but sometimes there were misunderstandings/disputes that resulted in breaking the ties of brotherhood to one another. The importance of implementing mutual understanding, mutual help, mutual respect, mutual trust and responsibility so that solidarity is maintained properly